Tradisi Mairiangan Jawi dari Pihak Bapak Mandeh Saat Walimatul Urs di Nagari Batu Gadang Kecamatan Sungai Geringging Kabupaten Padang Pariaman Perspektif Maslahah Mursalah - Iren Kalista; Muhammad Ridha (AHKAM, 2026)
Although the mairiangan jawi tradition performed by the bapak mandeh during walimatul urs in Nagari Batu Gadang continues to be maintained as part of customary practice, the obligation to provide a cow has the potential to impose an economic burden on those responsible for fulfilling it. This study aims to analyze the implementation process of the mairiangan jawi tradition and examine it from the perspective of maslahah mursalah. This study employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation involving the wali nagari, ninik mamak, and members of the Nagari Batu Gadang community. The data were analyzed using qualitative descriptive analysis through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the mairiangan jawi tradition was implemented through determining the day of the alek, delivering an invitation to the bapak mandeh, conducting a preparatory deliberation, providing a female cow, performing the mairiangan jawi procession, conducting a customary reception, and carrying out baetong. This tradition embodies the values of respect, mutual cooperation, solidarity, family responsibility, and economic support for the bridal couple. From the perspective of maslahah mursalah, the mairiangan jawi tradition can be maintained because it does not conflict with Islamic legal texts, provides tangible benefits, strengthens social bonds, and reinforces family relationships. However, its implementation must continue to consider the economic capacity of the bapak mandeh to avoid imposing an excessive burden. This study confirms that the mairiangan jawi tradition constitutes local wisdom that is consistent with the principles of Islamic law, provided that it is implemented proportionately, does not involve coercion, and prioritizes the realization of benefits and the prevention of harm.